Daddy's girl - Scottoline, Lisa (HarperCollinsPublishers, 2007)
Natalie Greco's humdrum life as a law professor is interrupted by a riot at the prison where she is teaching a class. In the chaos, a dying guard whispers to her, "Tell my wife it's under the floor." Though Nat escapes the riot, the guard's cryptic message puts her life in danger.